POTENTIAL ANALYSIS OF INDUSTRIAL WASTE USING SEVEN BASIC QUALITY TOOL PARETO DIAGRAM - Wiranto, Agus (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
The rapid development of the industrial sector in Indonesia today has an impact on other environments, both positive and negative impacts. The positive effects of industrial expansion are seen in sectors of the economy, many new jobs are created and many new applications for new technologies are used. The negative impact that cannot be avoided is caused by industrial waste, sometimes also caused by liquid waste containing substances that are harmful to the surrounding population. Every company must carry out industrial waste treatment from the negative impacts caused. PT TGLC, a company engaged in the manufacture of liquid sugar (glucose). In the process of producing liquid sugar (glucose) there is a regeneration process, namely the process of recovering the resin used in the ion exchanger column, which produces liquid waste in the process. Methods for dealing with the problem of industrial waste products, by identifying the contribution made by each system to the industrial data for all systems. The "Pareto Principle" was popularized by Joseph Juran, a business management consultant in 1950. Pareto analysis is used to identify the contribution made by each individual component of a system to the system. According to this analysis, 80% of the effect is due to 20% of the causes, 80% of the cost of reducing the risk results from 20% of the risks identified, and 80% of the value received comes from 20% of the benefits. In Pareto analysis A table is made of the reasons or causes and their frequency. Every industry has different problems. Every problem can be solved by applying the Pareto principle. For example, if you're not productive and you're always procrastinating, you can identify 20% of the reasons why your team isn't productive. by applying the Pareto Principle can increase productivity. This principle will encourage businesses to concentrate on areas that require extra resources to achieve efficiency. Therefore, companies only need to concentrate on the most important 20% aspects to deliver the expected 80% results. Companies will be stricter in distributing daily necessities and faster in rejecting unnecessary things if they understand this principle. Achievement Target Industrial waste that is generally produced by industrial waste or production process waste, then we must know how to manage it. A mandatory requirement from the Government that every industrial player must have is having a waste treatment plan. Any profits generated from industrial processes must be accompanied by waste treatment so as not to harm the environment. There are several types of waste treatment, according to each type of waste, to carry out waste management, we analyze it with the Pareto Principle, we can make a Pareto diagram to manage and manage waste. There are several steps that need to be done. First, collect data related to the problem for analysis. The data can include the type of issue, how it was measured, and the timing of the chart. The second step, carry out a more detailed identification. For example, the extent of damage to the product and what are its causes, the time and period of analysis should also be determined. The type of period in question can be a matter of days, weeks, or months. Next, we need to know the number of events to be analyzed. From these data, it can be created with bar graphs and line graphs. Then, the results can be communicated and become the basis for taking appropriate action for the company. The advantages of Pareto charts are that they are easier to read because they combine bar and line chart methods. In addition, it can more easily identify problems that occur within the company. The goal to be achieved in this study is to manage the potential of industrial waste, water regeneration in ion exchangers and may utilize liquid waste, using the application of the Decision Support System method or DSS (Decision Support System) Pareto diagram analysis